2003
DOI: 10.1099/mic.0.26323-0
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium avium subsp. paratuberculosis 35 kDa protein plays a role in invasion of bovine epithelial cells

Abstract: Mycobacterium avium subsp. paratuberculosis (M. paratuberculosis) enters intestinal epithelial cells of cattle and other ruminants via a mechanism that remains to be fully elucidated. This study showed that a gene encoding the M. paratuberculosis 35 kDa major membrane protein (MMP) is expressed at a higher level in low-oxygen and high-osmolarity conditions that are similar to the environment of the intestine. In addition, cattle with Johne's disease produced antibodies against MMP, suggesting that the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 35 publications
1
78
0
2
Order By: Relevance
“…Other studies have shown that unique sequences have considerable potential for use in the development of more specific and sensitive diagnostic assays for the detection of M. avium subsp. paratuberculosis infection by both molecular assay-and immunoassaybased approaches (2)(3)(4)40). It is also possible that these different amino acid sequences have significant impacts on the protein functions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that unique sequences have considerable potential for use in the development of more specific and sensitive diagnostic assays for the detection of M. avium subsp. paratuberculosis infection by both molecular assay-and immunoassaybased approaches (2)(3)(4)40). It is also possible that these different amino acid sequences have significant impacts on the protein functions.…”
Section: Discussionmentioning
confidence: 99%
“…In M. paratuberculosis, the accession number AF232752 is for a 35-kDa protein that is a surface protein and that appears to be expressed at higher levels under hyperosmolar conditions as compared to standard laboratory growth conditions (2). M. paratuberculosis cells have been shown to cross the intestinal mucosa by entering M cells in the terminal ileum (30), while M. avium interacts primarily with enterocytes and, to a lesser extent, with M cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for making PPDj and MpS are described in detail elsewhere. 1,25 Due to a lack of MpS antigen, only 80 of 110 sheep from the MAP-infected flocks and 123 of the 358 sheep from the MAP-noninfected flocks were tested with MpS. To reduce bias, systematic randomization was used to select the sheep tested with MpS.…”
Section: Methodsmentioning
confidence: 99%